EFFICACY OF ICON INFILTRATION RESIN TREATMENT FOR WHITE SPOT LESIONS - CASE REPORT - Maria Bolat; Carina Balcoș; Elena Dimitriu; Elena Raluca Baciu; Alice Murariu; Dana Gabriela Budală (Romanian Society of Oral Rehabilitation, 2021)
White spot lesions are defined as demineralization of the enamel surface, which does not form cavities and can be reversible. The resin infiltration technique has been used successfully in dentistry, preventing the evolution of dental caries in an early stage. ICON is a commercially available infiltration resin with low viscosity, consisting of a resin matrix based on methacrylate, initiators, and additives. One of the considerable advantages of this product is that it does not require the preparation of lesions, the treatment being atraumatic and without the use of anesthesia. The purpose of this presentation is to evaluate the aesthetic, functional efficacy of infiltration resin for a patient, immediately after treatment.